2013
DOI: 10.2903/j.efsa.2013.3451
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Flavouring Group Evaluation 21, Revision 4 (FGE.21Rev4): Thiazoles, thiophenes, thiazoline and thienyl derivatives from chemical groups 29 and 30

Abstract: The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids of the European Food Safety Authority was requested to evaluate 59 flavouring substances in the Flavouring Group Evaluation 21, Revision 4, using the Procedure in Commission Regulation (EC) No 1565/2000. This revision is made due to the inclusion of the assessment of new toxicity data on one supporting substance 5,6-dihydro-2,4,6-tris(2-methylpropyl)-4H-1,3,5-dithiazine , which is considered to be structurally related to the candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In FGE.21Rev4 (EFSA CEF Panel, 2013a ), based on experimental data on the supporting substance 2‐acetyl‐2‐thiazoline [FL‐no: 15.010], the CEF Panel concluded that 2‐methyl‐2‐thiazoline [FL‐no: 15.086] does not give rise to concern with respect to genotoxicity and it can accordingly be evaluated using the Procedure. In the same opinion, it was indicated that no data were provided for the substances in subgroup B‐III, because their evaluation was not supported by Industry (EFSA CEF Panel, 2013a ). Therefore, no genotoxicity data were available for the evaluation of 2,4‐dimethyl‐3‐thiazoline [FL‐no: 15.060] and 2‐isobutyl‐3‐thiazoline [FL‐no: 15.119].…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In FGE.21Rev4 (EFSA CEF Panel, 2013a ), based on experimental data on the supporting substance 2‐acetyl‐2‐thiazoline [FL‐no: 15.010], the CEF Panel concluded that 2‐methyl‐2‐thiazoline [FL‐no: 15.086] does not give rise to concern with respect to genotoxicity and it can accordingly be evaluated using the Procedure. In the same opinion, it was indicated that no data were provided for the substances in subgroup B‐III, because their evaluation was not supported by Industry (EFSA CEF Panel, 2013a ). Therefore, no genotoxicity data were available for the evaluation of 2,4‐dimethyl‐3‐thiazoline [FL‐no: 15.060] and 2‐isobutyl‐3‐thiazoline [FL‐no: 15.119].…”
Section: Assessmentmentioning
confidence: 99%
“…Therefore, no further data were submitted (DG SANCO, 2012, 2013) and these substances will not be considered any further (the 18 substances are listed in Table 2 ). Therefore, in FGE.21Rev4, the CEF Panel evaluated 41 substances (EFSA CEF Panel, 2013a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation